Dietary supplementation with blueberry partially restores T-cell-mediated function in high-fat-diet-induced obese mice. Issue 12 (30th May 2018) - Lewis, Erin D.; Ren, Zhihong; DeFuria, Jason; Obin, Martin S.; Meydani, Simin N.; Wu, Dayong
Abstract: Blueberry, rich in antioxidant and anti-inflammatory phytochemicals, has been demonstrated to lower inflammatory status in adipose induced by high-fat diet (HFD) and obesity. The effect of blueberry on systemic immune functions has not been examined. C57BL/6 mice were randomised to one of three diets – low-fat diet (LFD), HFD and HFD plus 4 % (w/w) blueberry (HFD+B) – for 8 or 12 weeks. Ex vivo T-cell mitogens (concanavalin A (Con A); phytohaemagglutinin), T-cell antibody (anti-CD3; anti-CD3/CD28)-stimulated T-cell proliferation and cytokine production were assessed. After 8 weeks, both HFD groups weighed more (>4 g) than the LFD group; after 12 weeks, HFD+B-fed mice weighed more (>6 g) and had 41 % more adipose tissue than HFD-fed mice ( P <0·05). After 12 weeks, T-cell proliferation was less in both HFD groups, compared with the LFD group. HFD-associated decrements in T-cell proliferation were partially (10–50 %) prevented by blueberry supplementation. At 12 weeks, splenocytes from HFD mice, but not from HFD+B mice, produced 51 % less IL-4 (CD3/CD28) and 57 % less interferon- γ (Con A) compared with splenocytes from LFD mice ( P <0·05). In response to lipopolysaccharide challenge, splenocytes from both HFD groups produced 24–30 % less IL-6 and 27–33 % less TNF- α compared with splenocytes from LFD mice ( P <0·05), indicating impaired acute innate immune response. By demonstrating deleterious impacts of HFD feeding on T-cell proliferation and splenocyte immune responses, our results provide insights into how HFD/obesity can disrupt systemic immune function. The protective effects of blueberry suggest that dietary blueberry can buttress T-cell and systemic immune function against HFD-obesity-associated insults.